Development of Nutritional Fulfillment Funds for Pregnant Women Using Web-Based Sugeno Method Case Study: "NURANI" Maternity Clinic and Maternity Hospital - Dita Mustika Anggraeni; Eko Prasetyo; M Mahaputra Hidayat (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
The high rate of malnutrition in various regions and the increasing prevalence of obesity, especially in big cities, is a double burden of nutritional problems in Indonesia. Meanwhile, the utilization of health facilities by those lower classes people in particular is still low and the health service itself is far from optimal. Besides, the pregnant women are also reluctant to consult their nutrients experienced during pregnancy. From the above problems, an application which can help pregnant women in making nutritional decisions at the time of pregnancy without consulting to consult a doctor / nutritionist was finnally made, that is Sugeno Fuzzy method. This method can provide the right nutritional decisions for pregnant women. The purpose of this study is to assist and facilitate pregnant women in the fulfillment of nutrition during pregnancy. Input used in this study is BMI, age of pregnant woman and age of pregnancy. While the output of the end result of this application system is to provide decisions about the nutrients experienced by pregnant women, they are less nutrition, ideal nutrition and excessive or much nutrition. The results of the experiment gives the calculation; the error rate of 62 % and the accuracy of 38 %.